Neoangiogenesis and the presence of progenitor cells in the venous limb of an arteriovenous fistula in the rat - Caplice, Noel M. (2007)
Venous injury and attendant venous stenosis are major contributors to the failure of hemodialysis vascular accesses. This report describes the presence of neoangiogenesis in the intima and adventitia of the venous limb of an arteriovenous (AV) fistula in the rat, the latter induced by creating an aortocaval fistula. Immunohistochemistry of the venous limb demonstrated the presence of c-Kit-positive cells lining new microvessels with lumen formation and that these c-Kit-positive cells exhibited either a smooth muscle phenotype as reflected by concomitant expression of calponin, or an endothelial phenotype as reflected by expression of endothelial nitric oxide synthase (eNOS). Western analysis confirmed upregulation of eNOS in the venous limb of the AV fistula. Measurement of systemic concentrations of angiogenic cytokines, namely, monocyte chemotactic protein-1, stromal cell-derived factor-1 (SDF-1), cytokine-induced neutrophil chemoattractant, and VEGF, failed to reveal an increase in these cytokines either at 3 or 10 wk after creation of the AV fistula. The angiogenic cytokines VEGF and SDF-1 were not upregulated in the venous limb of the AV fistula either at 2 or 16 wk. We conclude that in this model of an AV fistula in the rat, neoangiogenesis occurs and is constituted, at least in part, by bone marrow-derived cells, the latter differentiating to exhibit either an endothelial or smooth muscle phenotype. In view of these findings, we suggest that this model may offer an experimental approach by which to explore the evolution and significance of neoangiogenesis in the formation and pathobiology of vascular plaques, and the mechanisms that promote dysfunction of hemodialysis AV fistulas.